2019
DOI: 10.1021/acs.jpcc.9b00649
|View full text |Cite
|
Sign up to set email alerts
|

CO-Induced Aggregation and Segregation of Highly Dilute Alloys: A Density Functional Theory Study

Abstract: Highly dilute binary alloys composed of an active platinum group metal (PGM) and a more inert coinage metal are important in the field of catalysis, as they function as active and selective catalysts. Their catalytic properties depend on the surface "ensemble" of PGM atoms, whose size may be altered under reactive conditions. We use density functional theory and investigate the interaction of CO, a molecule common in numerous industrially important chemistries, with alloys that are composed of a PGM (Pt, Pd, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 74 publications
3
74
0
Order By: Relevance
“…11 Interestingly, the binding of adsorbates on SAA isolated dopant atoms is often weaker as compared to a pure dopant catalyst, which allows for the facile desorption of products and tolerance to common poisons. [12][13][14][15][16][17] Though their application has been met with resounding success in the catalysis of a number of chemical processes, the use of SAAs is not ubiquitous. In some instances, dispersed dopant atoms are not capable of activating chemical bonds, with this task requiring contiguous active dopant metal sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Interestingly, the binding of adsorbates on SAA isolated dopant atoms is often weaker as compared to a pure dopant catalyst, which allows for the facile desorption of products and tolerance to common poisons. [12][13][14][15][16][17] Though their application has been met with resounding success in the catalysis of a number of chemical processes, the use of SAAs is not ubiquitous. In some instances, dispersed dopant atoms are not capable of activating chemical bonds, with this task requiring contiguous active dopant metal sites.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is well-known that the alloy structure and composition strongly affect the adsorption energy of surface intermediates [23][24][25][26] and the catalytic performance during a chemical process. 27 Accordingly, a number of experimental and theoretical studies investigating the structure of alloy systems under vacuum [28][29][30][31][32] versus reactive conditions 13,14,20,22,[33][34][35][36][37][38][39][40][41] (i.e. in the presence of adsorbates) have appeared in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have explored the adsorption of CO on the top dopant site of a number of Cu-, Ag-, and Aubased SAA surfaces. 18,39 A highlight of our work was that the binding strength of CO on SAA(111) and (100) surfaces is almost identical. 18 Therefore, our results suggested that isolated dopant atoms on flat facets show very similar reactivity, which appears to be independent of the geometry of the catalytic surface.…”
Section: Resultsmentioning
confidence: 83%
“…18,39 A highlight of our work was that the binding strength of CO on SAA(111) and (100) surfaces is almost identical. 18 Therefore, our results suggested that isolated dopant atoms on flat facets show very similar reactivity, which appears to be independent of the geometry of the catalytic surface. To some extent, this phenomenon can be attributed to the limited electronic and spatial overlap between the dopant atom and its surrounding host metal atoms.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation